Interpretation of the Verse of Fawatih Al-Suwar Using Sighat Amr and Istifham Perspectives of Fakhr Al-Razi and Al-Thabari - Rama Yulis; Syafruddin Syafruddin; Syofyan Hadi; Syarifatus Shalihah Khairati (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This study aims to understand the meaning of the commentators in explaining the verses of Fawatih Al-Suwar using Sighat Amr and Istifham using the Muqaran approach. This research uses qualitative methods in library research (Library Study). The study results can be locked that the control of fakhr al-Razi against the Fawatih al-Suwar verse by using Sighat Amr in the letters of Jin, Al-Alaq and Al-Kafirun. The command of Allah SWT the Prophet Muhammad SAW, storage using sighat istifham in the letters Insan and Al -Maun is an interrogative sentence that means affirmation in Surah Al-Naba’ the sentence means affirmation big news. Then according to Al-Thabari in supervising the verse of Fawatih Al-Suwar by using sighat Amr in the letters of Jin and Al-Alaq meaningfully to the Prophet Muhammad and Al-Kafirun’s letter is a warning order to the murikin. In contrast, sighat istifham in Surah Al-Insan and Al-Maun is an interrogative sentence that means affirmation. In Surah Al-Naba’ it is an interrogative sentence that means enormous news.